LEARNING CYCLE MANAGEMENT BASED ON LOCAL WISDOM IN INSTILLING THE CHARACTER OF RELIGIOUS STUDENTS IN MADRASA - Masruroh, Siti; Bz, Zakiyah (PEDAGOGIK : JURNAL PENDIDIKAN, 2022)
The subjects of this study were students of MI Nurur Rahmah. The data analysis technique used is descriptive qualitative analysis, and the data collection technique used is the method of observation and interviews. The local wisdom that exists at MI Nurur Rahmah is part of the habits that are believed and obeyed by students and teachers at MI Nururrahmah, which are religious habits or practices that occur every day, such as congregational prayers, dhuha prayers, and reading the Qur'an. before the KBM starts. As a source of learning and the cultivation of local wisdom character values that can be instilled in students' personalities,Based on the results of research and discussion on inculcating students' religious character, the management of the learning cycle based on local wisdom applied by MI teacher Nurur Rahmah aims to make students better understand the meaning of piety in religious rituals, so that the religious values contained therein can be instilled in students with the hope of becoming their religious character later by instilling the religious character of students through habituation in the institution.